2019
DOI: 10.1080/09638288.2019.1693643
|View full text |Cite
|
Sign up to set email alerts
|

Preferences regarding the way of use and design of a work ability prognosis support tool: a focus group study among professionals

Abstract: Purpose: To explore the preferable way of use and design of a work ability prognosis support tool for insurance physicians (IPs) and labour experts (LEs), based on a prediction model for future changes in work ability among individuals applying for a work disability benefit. Methods: We conducted three focus groups with professionals of the Dutch Social Security Institute (17 IPs and 7 LEs). Data were audio recorded and qualitatively analysed according to the main principles of thematic analysis. Results: Clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In the present study, IPs first made their own prognosis and subsequently evaluated the decision support tool. Although this is in line with the results of a previous study, in which professionals indicated that they would first want to make their own prognosis and afterwards verify or adjust their evaluation based on the outcome of decision support tool, this might have lowered the efficacy of the tool [11]. Presenting the tool at the beginning of the decision-making process might increase its efficacy by making the tool part of this process.…”
Section: Implications For Research and Practicesupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, IPs first made their own prognosis and subsequently evaluated the decision support tool. Although this is in line with the results of a previous study, in which professionals indicated that they would first want to make their own prognosis and afterwards verify or adjust their evaluation based on the outcome of decision support tool, this might have lowered the efficacy of the tool [11]. Presenting the tool at the beginning of the decision-making process might increase its efficacy by making the tool part of this process.…”
Section: Implications For Research and Practicesupporting
confidence: 86%
“…a decision support tool. Based on professionals' preferences regarding the way of use and design of the tool, we developed such a tool [11]. The tool uses claimant-specific information from self-reported questionnaires and registration data from the Dutch Social Security Institute (SSI) [21].…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose a qualitative method (focus groups and interviews) due to the limited prior research and our desire to obtain a richer and more in-depth view of this programme from participants’ perspective. Focus groups also allow participants to interact and build on each other’s ideas and knowledge of the programme (Louwerse et al, 2019; Riesen & Morgan, 2018). Thus, focus groups have the potential to uncover strengths, barriers and limitations to the programme implementation.…”
Section: Overview Of Current Studymentioning
confidence: 99%
“…This demand was also reported in other studies [ 26 , 30 ], which led to research providing potential search strategies, filters, or strings regarding themes such as prognosis and work participation [ 30 32 ]. The desire for user-friendliness, simplicity, and help in overseeing the various prognostic aspects was also identified by Kox et al [ 8 ] and Louwerse et al [ 33 ], both of whom were exploring possible prognostic tools. In contrast, when presented with possible prognostic tools, physicians also stressed the importance of preserving their professional autonomy to make unique, tailored evaluations.…”
Section: Discussionmentioning
confidence: 97%